QAIDAH KHUSUS DALAM EKONOMI ISLAM - Baiq Hija Farida (Jurnal Pelita Nusa, 2021)
ABSTRACT This rule of Fiqh is used as a basis for the daily activities of Muslims to understand the meaning of Islamic teachings (maqashid al-syari'ah) more comprehensively. The term fiqh rules is a translation from the Arabic alqawaid al-fiqhiyah. Al-qawaid is a plural (plural) form of the word al-qaidah which linguistically means basic, rules or general criteria. According to ushul experts and jurists, an understanding of qawa'id Fiqhiyyah is necessary to perform an ijtihad or renewal of thought in matters of worship, muamalah, and priority scales. According to Musthafa az-Zarqa, Qowaidul Fiqhyah are the basics of fiqh that are general and concise in the form of laws that contain the general syara 'laws on various legal events that fall within the scope of the rules. The specific fiqh rule is a rule that specifically discusses certain areas of study, hence the need for the community to know about this fiqh rule. In the division of the field, the rules of fiqh are specifically grouped into several parts, among others in the field of worship mahdhah, ahwal asy-syakhshiyyah, muamalah, jinayah, siyasah, and alaqdiyah. The specific rules of fiqh related to Islamic economics are aqad (transactions), mal (wealth assets), banking and arbitration. Keywords : Fiqh Rules, Special Rules, Islamic Economics.